Pengaruh Kualitas Layanan dan Pengalaman Pelanggan Terhadap Kepuasan Pelanggan Pada Wisata Petik Anggur Brazil Di Pondok SVD Pancasari - Mutia, Salsabilla; Ariasih, Made Putri (Cattleya Darmaya Fortuna, 2026)
The focus of this research is to examine how service quality and customer experience affect customer satisfaction at wisata petik anggur brazil di Pondok SVD Pancasari. The approach applied in this research is quantitative casual. The sample of this research comprised costumers as well as visitors who came to the wisata petik anggur brazil di Pondok SVD Pancasari. The research population included all individuals who had previously or were currently visiting the tourism site, with sample determination using non-probability sampling technique involving 120 respondents. Service quality (X1) and customer experience (X2) were established as independent variables, while customer satisfaction (Y) served as the dependent variable. Data retrieval was performed through questionnaire distribution and subsequently processed using SPSS 26.0 software using multiple linear regression analysis method. Based on the research findings obtained, it can be concluded that (1) service quality has a positive and significant influence on customer satisfaction, (2) customer experience is also proven to have a positive and significant influence on customer satisfaction, and (3) simultaneously, service quality and customer experience together provide a positive and significant influence on customer satisfaction of the wisata petik anggur brazil di Pondok SVD Pancasari.